Intraflagellar transport protein 88 interacts with polycystin 2 to regulate mechanosensitive hedgehog signaling in mandibular condylar chondrocytes. (November 2022) - Wang, Zhuo; Sa, Guoliang; Zheng, Liwu; Wei, Zequan; Zhang, Zhuoyu; Hu, Yanping; Yang, Xuewen
Abstract: Objective: This study aimed to explore whether intraflagellar transport protein 88 (IFT88) was associated with polycystin 2 during mechanotransduction of mandibular condylar chondrocytes. Methods: Rat mandibular condylar chondrocytes ﻿isolated from the condylar bone-cartilage junction were subjected to cyclic tensile strain (0.1 Hz, 10% elongation). Overexpression of IFT88 was achieved by lentiviral vector-mediated transfection. Knockdown of IFT88 and polycystin 2 was achieved by small interfering RNA (siRNA). The prevalence and length of cilia were reflected by immunofluorescence staining. The activities of hedgehog signaling were evaluated by western blot analysis. The interaction between polycystin 2 and IFT88 was evaluated by conducting a co-immunoprecipitation (co-IP) assay. Results: Overexpression of IFT88 increased the length of cilia. Protein levels of polycystin 2, Indian hedgehog (Ihh), Patched 1 (Ptch1), Smoothened (Smo), and Glioma-associated oncogene homolog 1 (Gli1) were elevated in IFT88-overexpressing mandibular condylar chondrocytes under cyclic tensile strain. Knockdown of the protein level of IFT88 reduced the prevalence and length of cilia, and protein levels of polycystin 2, Ihh, Ptch1, Smo, and Gli1. A co-IP assay showed that IFT88 formed a complex with polycystin 2 under cyclic tensile strain. Knockdown of polycystin 2 decreased the protein levels of IFT88, Ihh, Ptch1, Smo, and Gli1 in mandibular condylar chondrocytes following cyclic tensile strain. Conclusion: These findings highlight the vital role of an interaction between IFT88 and polycystin 2 in mechanosensitive hedgehog signaling in mandibular condylar chondrocytes following cyclic tensile strain, which suggest that therapies regulating polycystin 2 may be considered for the disorders of temporomandibular joints. Highlights: IFT88 is necessary for mechanosensitive hedgehog signaling in condylar chondrocytes. Polycystin 2 is required for mechanosensitive hedgehog signaling. IFT88 co-immunoprecipitated with ﻿polycystin 2 under cyclic tensile strain.